LIGHT-INDUCED RICE1 Regulates Light-Dependent Attachment of LEAF-TYPE FERREDOXIN-NADP+ OXIDOREDUCTASE to the Thylakoid Membrane in Rice and Arabidopsis. Issue 3 (3rd March 2016) - Yang, Chao; Hu, Hongtao; Ren, Hongyan; Kong, Yuzhu; Lin, Hongwei; Guo, Jiangfan; Wang, Lingling; He, Yi; Ding, Xiaomeng; Grabsztunowicz, Magda; Mulo, Paula; Chen, Tao; et al.
Abstract : Light-dependent degradation of LIR1 regulates the distribution of LFNR, which may play an important role in the allocation of reducing power depending upon environmental conditions. Abstract: LIR1 ( LIGHT-INDUCED RICE1 ) encodes a 13-kD, chloroplast-targeted protein containing two nearly identical motifs of unknown function. LIR1 is present in the genomes of vascular plants, mosses, liverworts, and algae, but not in cyanobacteria. Using coimmunoprecipitation assays, pull-down assays, and yeast two-hybrid analyses, we showed that LIR1 interacts with LEAF-TYPE FERREDOXIN-NADP + OXIDOREDUCTASE (LFNR), an essential chloroplast enzyme functioning in the last step of photosynthetic linear electron transfer. LIR1 and LFNR formed high molecular weight thylakoid protein complexes with the TIC62 and TROL proteins, previously shown to anchor LFNR to the membrane. We further showed that LIR1 increases the affinity of LFNRs for TIC62 and that the rapid light-triggered degradation of the LIR1 coincides with the release of the LFNR from the thylakoid membrane. Loss of LIR1 resulted in a marked decrease in the accumulation of LFNR-containing thylakoid protein complexes without a concomitant decrease in total LFNR content. In rice ( Oryza sativa ), photosynthetic capacity of lir1 plants was slightly impaired, whereas no such effect was observed in Arabidopsis thaliana knockout mutants. The consequences of LIR1 deficiency in different species are discussed.